2022
DOI: 10.1001/jamanetworkopen.2022.47649
|View full text |Cite
|
Sign up to set email alerts
|

Racial and Ethnic Differences in Internal Medicine Residency Assessments

Abstract: ImportancePrevious studies have demonstrated racial and ethnic inequities in medical student assessments, awards, and faculty promotions at academic medical centers. Few data exist about similar racial and ethnic disparities at the level of graduate medical education.ObjectiveTo examine the association between race and ethnicity and performance assessments among a national cohort of internal medicine residents.Design, Setting, and ParticipantsThis retrospective cohort study evaluated assessments of performance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 48 publications
1
12
1
Order By: Relevance
“…It is also possible that disparities and potential biases related to gender and race and ethnicity might have affected Milestones ratings and/or patient complaints. 30 , 31 , 32 , 33 In the present study, we found no difference in the proportion rated as below target for the Milestones by gender and no difference in the proportion with patient complaints by gender. Because the ACGME data during the study period did not have reliable race and ethnicity data, we were not able to include these variables in the current study.…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…It is also possible that disparities and potential biases related to gender and race and ethnicity might have affected Milestones ratings and/or patient complaints. 30 , 31 , 32 , 33 In the present study, we found no difference in the proportion rated as below target for the Milestones by gender and no difference in the proportion with patient complaints by gender. Because the ACGME data during the study period did not have reliable race and ethnicity data, we were not able to include these variables in the current study.…”
Section: Discussioncontrasting
confidence: 63%
“…It is also possible that disparities and potential biases related to gender and race and ethnicity might have affected Milestones ratings and/or patient complaints . In the present study, we found no difference in the proportion rated as below target for the Milestones by gender and no difference in the proportion with patient complaints by gender.…”
Section: Discussionmentioning
confidence: 99%
“…Racial disparities in UME performance evaluations extend beyond the narrative evaluations to application elements used by residency program directors to make admissions decisions, 16 including clinical clerkship grades and standardized summative evaluations, 17 and Alpha Omega Alpha honor society membership. 18 Disparities in performance assessments persist into graduate medical education and have been demonstrated in standardized resident milestone assessments for internal 19,20 and EM. 21,22 Similar to the UME findings, these studies show that residents who are female 19,21,22 or from a URM group 20 are consistently rated as less skilled than their male and non-URM counterparts.…”
Section: Introductionmentioning
confidence: 99%
“…[23][24][25][26][27] During training, URiM trainees also receive lower assessment scores compared to their colleagues, which can lead to an amplification cascade that negatively affects future career goals. [28][29][30] Further, the current learning environment does not fully support the challenge minority residents face in balancing their professional development and identity. 24 This burden is coupled with a disproportionate expectation to contribute to programmatic diversity, equity, and inclusion efforts.…”
mentioning
confidence: 99%
“…URiM trainees disproportionately suffer from discrimination, racial harassment, and microaggressions in the clinical environment and are more likely to withdraw from residency training and take extended leaves of absence 23–27 . During training, URiM trainees also receive lower assessment scores compared to their colleagues, which can lead to an amplification cascade that negatively affects future career goals 28–30 . Further, the current learning environment does not fully support the challenge minority residents face in balancing their professional development and identity 24 .…”
mentioning
confidence: 99%